A Necessidade de Orientação Urbanística - Barberis, Beatriz Araujo Lara (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 1990)
This article shows the disordered growth, the lack of harmony in the residential districts in vertical, and the careless process, that has created its urban design. It reinforces the necessity that this urban space must be organized from the antecipate purposes of the use of the ground, that contain urbanistic orientation, that results in a design that begets a better environmental quality